Autophagy suppresses RIP kinase-dependent necrosis enabling survival to mTOR inhibition. - Kevin Bray; Robin Mathew; Alexandria Lau; Jurre J Kamphorst; Jing Fan; Jim Chen; Hsin-Yi Chen; Anahita Ghavami; Mark Stein; Robert S DiPaola; Donna Zhang; Joshua D Rabinowitz; et al. (PLoS ONE)
mTOR inhibitors are used clinically to treat renal cancer but are not curative. Here we show that autophagy is a resistance mechanism of human renal cell carcinoma (RCC) cell lines to mTOR inhibitors. RCC cell lines have high basal autophagy that is required for survival to mTOR inhibition. In RCC4 cells, inhibition of mTOR with CCI-779 stimulates autophagy and eliminates RIP kinases (RIPKs) and this is blocked by autophagy inhibition, which induces RIPK- and ROS-dependent necroptosis in vitro and suppresses xenograft growth. Autophagy of mitochondria is required for cell survival since mTOR inhibition turns off Nrf2 antioxidant defense. Thus, coordinate mTOR and autophagy inhibition leads to an imbalance between ROS production and defense, causing necroptosis that may enhance cancer treatment efficacy.